MILLENNIAL GENERATION CULTURAL BEHAVIOR IN USE OF INSTAGRAM FOR OBJECT TOURISM PROMOTION IN BALI - Hanindharputri, Made Arini; Pradnyanita, A. A. Sagung Intan (International Conference on Cultural Studies, 2018)
The presence of the internet today is very useful for people’s lives, by providing convenience in communicating or finding the desired information. One generation that is very familiar with the internet and social media is the millennial generation, or known as the Y and Z generations. This generation makes social media as a medium for sharing information and experiences, even to interact with fellow users of social media. This also happens in Indonesia, where according to survey of the Association of Indonesian Internet Service Providers (APJII), millennial generation access more social media than by visiting other content such as mass media portals, knowledge sites, expert blogs, or e-book subscriptions. Millennial generation cultural behavior that uses the internet and social media to obtain information can be an opportunity for creative actors to promote attractions in Bali. In the present era, the promotion of tourist attraction is no longer effective using conventional media such as print media. The use of social media is considered cheaper, faster and more credible and certainly in accordance with the habits of millennial generation people today. Seeing these opportunities, research was made to examine the use of social media, especially Instagram, as a media campaign and its relation to millennial generation culture. The participants are Visual Communication Design students of STD Bali by making e-post works to promote tourism object in Bali. The design process begins with research to determine the potential of tourist attractions, design ideas, and visualization design. Instagram selected as a social media platform because according to the survey, Instagram become the medium of contemporary with the most number 2 of users in Indonesia. The objective of the research is to know the extent to which millennial generations can be use social media positively and promote the potential of local tourism objects in Bali with the target of millennial generation itself.